Effect of Biochar on Composting of Cow Manure and Kitchen Waste - Felicien Sebahire; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Jean Nduwamungu (Land)
Composting is a common method for managing organic waste and creating nutrient-rich soil amendments. Recently, biochar, a carbon-rich material from biomass pyrolysis, has been noted for potentially improving composting. This study examines the impact of adding biochar to compost made from cow manure and kitchen waste through a controlled lab experiment. The treatments were labeled as CMX (cow manure), KWX (kitchen waste), and CMKWX (both) with X being the percentage of CM, KW, and CMKW minus that of biochar in the mixture. Key parameters such as temperature (T), pH, and electric conductivity (EC) were tracked during the composting processes, and the final composts were analyzed for total nitrogen (N), available nitrogen (AN), total phosphorus (TP), available phosphorus (AP), total potassium (TK), organic carbon (OC), calcium (Ca2+), magnesium (Mg2+), and organic matter (OM). The results showed that adding less than 10% biochar influenced composting positively. Specifically, 5% biochar amendment led to higher thermophilic temperatures (45–57 °C) and stable pH levels (6.3–8.7) compared to controls. However, biochar did not significantly enhance EC, which peaked at 1.78 dS/m in both the control and 5% biochar treatments. Nutrient analysis revealed that biochar increased Ca2+ (13.62 meq/g) and Mg2+ (5.73 meq/g) retention in CM composts (CM85 and CM100). The highest OM content was 16.84% in CM90, while the lowest was 3.81% in CM95. Higher OM negatively affected TN, with CM treatments having more OM and KW treatments having more TN. TP and TK were higher in control treatments without biochar. This study highlights the benefits of integrating biochar with organic waste for enhancing compost nutrient profiles and soil fertility. It was observed that the more diverse the compost feedstock, i.e., CMKW, the higher the nutrient content for treatments containing less than 10% biochar.